PkM Pendampingan Potensi Biodiversitas Sebagai Rintisan Desa Wisata di Banjar Pukuh, Desa Tiga, Susut, Bangli - Ni Putu Widya Astuti; I Wayan Rosiana (IAHN Gde Pudja Mataram, 2026)
Banjar Pukuh administratively located in Tiga Village, Susut District, Bangli Regency. Pukuh located in a highland area with temperatures suitable for agricultural areas. Most of the Pukuh Village community currently works in the agricultural sector by cultivating rice fields to produce rice and secondary crops. Besides these two commodities, Pukuh Village also very suitable forplantations such as citrus fruit which is a mainstay commodity in the economy of people in Banjar Adat Pukuh. Residents of the Banjar Adat Pukuh have a unique and traditional of building residential houses where the community will build houses on the east side and abstain from building houses on the west side of the road. This is one of the unique things about this village and not widely people known. The challenges faced by partners in preparing Banjar Pukuh as a tourist village are that they do not have knowledge about ecotourism activities, they do not have knowledge about landscaping areas for ecotourism activities, partners do not have knowledge about how to inventory animals biodiversity and partners do not have knowledge and skills regarding organic waste management. The solution to this partner problem is to provide assistance in the form of providing socialization and improving skills by conducting training. The results of this mentoring activity are an increase in partners' knowledge regardingtourism villages by 85%, an increase in knowledge related to socialization regarding how to inventory animals, partners'understanding has increased by 90%, an increase in knowledge related to socialization regarding processing pig waste, an increase in knowledge by 90% and skills. processing of pig manure waste by 80%.